A-1: OMISSION OF THE DESCRIBED AND ITS RHETORICAL PURPOSES IN THE HOLY QURAN: حذف الموصوف: أغراضه، وأسراره البلاغية في القرآن الكريم - Tahir, Mohib ul nabi; Al-Azhari , Sanaullah Rana; Yousaf Khan, Abdul Rehman (International Journal of Islamic Business, Administration and Social Sciences (JIBAS), 2024)
The study addresses the method of Omission of the described (حذف الموصوف) and its Rhetorical purposes in the holy Quran in many ways. The omission of the described is investigated as a stimulant method that refreshes the reciter’s brain and tests his mind capacity, makes him think differently, and focuses deeply on the verses of the holy Quran. The study explains the effect of the omission on the meaning of the Quranic text, farther more it reveals the aesthetic beauty in the style of omission in the holy Quran that lets the leader virtue of meditation and interact and with text by estimating the omitted part and filling voids in the text. The study shows the effect of omission style on the reader and listener who understands the aesthetic secrets of that method. We also analyze some verbal omissions that help readers and listeners. In the last of the research paper. we try to discuss and shed light on the outstanding result of omission style in the holy Quran.